The big questions of public administration education - Denhardt, Robert B. (2001)
Following Behn's observation that scientists in other fields understand the big questions of their disciplines and focus attention and their discussions on those questions, public administration scholars have attempted to identify the "big questions" in public management and public administration. In this article, I suggest that scholars in public administration should also be attentive to the big questions of public administration education, those timeless and enduring concerns that speak to the basic perspectives that we bring to the educational process. Specifically, I identify four big questions: Do we seek to educate our students with respect to theory or to practice? Do we prepare students for their first jobs or for those to which they might aspire later? What are the appropriate delivery mechanisms for MPA courses and curricula? What personal commitments do we make as public administration educators? I argue that these big questions in public administration education are far more connected than we usually think, and by posing these questions in terms of processes of human development we can at least provide a framework through which we might develop more coherent answers to these big questions, answers that recognize and build on the diversity of our students and our faculty. - Reproduced
Keywords: Public administration